Pengaruh Job Insecurity Dan Job Stress Terhadap Turnover Intention Di Hotel Yuan Garden Pasar Baru - Vanny Sisca Amelia; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research motivation is the researchers' observations regarding turnover intention at the Yuan Garden Hotel, Pasar Baru. Job insecurity and job stress are factors that influence turnover intention at the Yuan Garden Pasar Baru Hotel. The research purpose is to reveal and describe the job insecurity impact and job stress on turnover intention at the Yuan Garden Pasar Baru hotel. This type of research is quantitative descriptive with a sampling technique using purposive sampling and a sample size of 60 respondents based on a saturated sampling formula. The technique for data collection in this research uses a questionnaire with a Likert scale which has been tested for validity and reliability. The collection for is analyzed using multiple linear regression analysis with the support by SPSS (Statistics Product and Service Solution) calculation tool version 27.00. Based on the analysis results, conclusions shown on the t-test results, for the variable job insecurity (X1) with a level of significant is 0.001 < 0 .05, meaning there is a significant influence of job insecurity on turnover intention. Meanwhile, the t-test results for the job stress variable (X2) have a level of significance is 0.393 < 0.05, meaning that job stress has no significant effect on turnover intention. Based on the f-test with a level of significance is 0.000 < 0.05, this means that simultaneously job insecurity (X1) and job stress (X2) have a significant effect on turnover intention. The job insecurity (X1) and job stress (X2) variables influence the turnover intention (Y) variable by 37.6% while the remaining 62.4% is influenced by other variables.